2021
DOI: 10.1097/ncc.0000000000000970
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reiki Therapy on Quality of Life and Fatigue Levels of Breast Cancer Patients Receiving Chemotherapy

Abstract: Background The quality of life of patients receiving chemotherapy decreases, and fatigue is one of the most common symptoms. Reiki is used for cancer patients as an energy-based complementary and alternative method. Objective The aim of this study was to determine the effect of Reiki therapy on the quality of life and fatigue levels in breast cancer patients receiving chemotherapy. Methods This was a pretest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…9 A different study wherein fatigue was studied also reported that Reiki application was effective in lowering fatigue levels. 22 Other studies with different samples have also revealed that Reiki reduces fatigue levels. 11,23,24 The result in our study that Reiki applied in HD patients reduced their fatigue levels was compatible with the results of the studies mentioned earlier.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…9 A different study wherein fatigue was studied also reported that Reiki application was effective in lowering fatigue levels. 22 Other studies with different samples have also revealed that Reiki reduces fatigue levels. 11,23,24 The result in our study that Reiki applied in HD patients reduced their fatigue levels was compatible with the results of the studies mentioned earlier.…”
Section: Discussionmentioning
confidence: 95%
“…It was determined in a study conducted with adolescents with dysmenorrhea that the Reiki intervention resulted in a decrease in general fatigue levels 9. A different study wherein fatigue was studied also reported that Reiki application was effective in lowering fatigue levels 22. Other studies with different samples have also revealed that Reiki reduces fatigue levels 11,23,24.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of benefits for patients, many studies and review papers have examined the efficacy of receiving hands on Reiki. Much research focuses on patients with cancer where Reiki has been linked to decreased distress, anxiety, depression, fatigue, agitation, pain, and nausea, and improved sleep and quality of life [ [9] , [10] , [11] , [12] , [13] ]. A review found it significantly reduced cancer related pain [ 14 ].…”
Section: Introductionmentioning
confidence: 99%